INDONESIAN INTERESTS IN COOPERATION WITH THE CZECH REPUBLIC IN THE FIELD OF DEFENSE 2015-2018 - Bayu Lesmana; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Indonesia is working to improve its country's defense strength. Indonesian defense equipment is currently is not in a optimal condition to support Indonesia's defense. In addition to striving to improve its defense systems, Indonesia also strives to increase the independence of its defense industry to creat an independent country and reduce dependency with other countries. The sources of this research were obtained through literature reviews, books, websites, and others. The source of analysis is qualitative methods. This study uses the level of analysis of the nation state, neorealism perspective that illustrates that every country does not have to pursue strength but also must work together and the theory of International Cooperation as an answer for countries of the world international. To increase its defense strength, Indonesia is conducting defense cooperation with other countries, one of the countries that is Indonesia's defense cooperation partner, is the Czech Republic. This aims of thesis is to explain the existence of this collaboration is expected to improve Indonesia's defense capabilities and create an independent defense industry. Key Words: International Cooperation, Defense, Minimum Essential Force, Indonesian Defense Industry.